Preparation and properties of buckypaper-gold nanoparticle composites - GOUNKO, IOURI; BYRNE, MICHELE THERESE; HANLEY, CORMAC (My University, 2010)
Highly conductive buckypaper-gold nanoparticles composites have been prepared by the in situ electroless deposition of gold nanoparticles during the filtration that resulted in increases in conductivities of up to 684% at very low gold content.
PUBLISHED
Keywords: Physical Chemistry; Nanotubes; gold; Nanoscience & Materials